2013
DOI: 10.5966/sctm.2013-0020
|View full text |Cite
|
Sign up to set email alerts
|

Progranulin, a Major Secreted Protein of Mouse Adipose-Derived Stem Cells, Inhibits Light-Induced Retinal Degeneration

Abstract: The authors examined the protective effects of adipose‐derived stem cells and adipose‐derived stem cell‐conditioned medium (ASC‐CM) against retinal damage and identified the neuroprotective factors in ASC‐CM. The findings suggest that ASC‐CM and progranulin have neuroprotective effects in the light‐induced retinal‐damage model. Progranulin may be a potential target for the treatment of the degenerative diseases of the retina.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 40 publications
2
44
2
Order By: Relevance
“…If Progranulin and the lysosomal/proteolytic pathway could be upregulated, it is possible that excess lipopigment accumulation could be reversed in these patients prior to the degeneration of neurons. A recent study showed that Progranulin is a secreted factor of adipose-derived stem cells and shows protective effects against light-induced retinal damage in vivo (Tsuruma et al, 2013), suggesting that Progranulin may have neuroprotective properties.…”
Section: Discussionmentioning
confidence: 99%
“…If Progranulin and the lysosomal/proteolytic pathway could be upregulated, it is possible that excess lipopigment accumulation could be reversed in these patients prior to the degeneration of neurons. A recent study showed that Progranulin is a secreted factor of adipose-derived stem cells and shows protective effects against light-induced retinal damage in vivo (Tsuruma et al, 2013), suggesting that Progranulin may have neuroprotective properties.…”
Section: Discussionmentioning
confidence: 99%
“…Another study identified a factor called progranulin as a major secreted protein of ADMSCs which showed protective effects against retinal damage both in vitro and in vivo. These findings suggest that ADMSCs have neuroprotective effects in the light-induced retinal damage model [26]. …”
Section: Discussionmentioning
confidence: 99%
“…ASCs express a number of biological proteins involved in the promotion of cell viability, including transforming growth factor β 1 (27,33) and progranulin (34). However, numerous studies have demonstrated the anti-proliferative or anti-tumorigenic effects of ASCs.…”
Section: Ink4amentioning
confidence: 99%
“…ASCs produce various growth factors and adipokines, thus, the cells function as an endocrine or paracrine organ that is considered to perform a pivotal role in maintaining a suitable microenvironment for the regulation of tumor initiation, progression and metastasis (27,(33)(34)(35). ASCs express a number of biological proteins involved in the promotion of cell viability, including transforming growth factor β 1 (27,33) and progranulin (34).…”
Section: Ink4amentioning
confidence: 99%